On the importance of prior relationships in bank loans to retail customers - Manju Puri; Jörg Rocholl; Sascha Steffen (European Central Bank (ECB), 2011)
This paper analyzes the importance of retail consumers' banking relationships for loan defaults using a unique, comprehensive dataset of over one million loans by savings banks in Germany. We find that loans of retail customers, who have a relationship with their savings bank prior to applying for a loan, default significantly less than customers with no prior relationship. We find relationships matter in different forms, scope, and depth. Importantly, though, even the simplest forms of relationships such as transaction accounts are economically meaningful in reducing defaults, even after controlling for other borrower characteristics as well as internal and external credit scores. Our results suggest that relationships of all kinds have inherent private information and are valuable in screening, in monitoring, and in reducing consumers' incentives to default.
Keywords: G20; G21; 330; default rates; monitoring; relationships; Retail banking; screening